2020
DOI: 10.3390/metabo10020061
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating COMP and YKL-40 as Markers of Metabolic Changes of Cartilage with Adipocytokines in Juvenile Idiopathic Arthritis

Abstract: The aim of this study was to evaluate the association of circulating cartilage oligomeric matrix protein (COMP) and human cartilage glycoprotein-39 (YKL-40) as markers of metabolic changes of cartilage, with leptin, adiponectin, and resistin in juvenile idiopathic arthritis (JIA) patients before and after treatment. A significant decrease of COMP and an increase of YKL-4 were found in blood of untreated patients. JIA treatment leading to clinical improvement resulted in normalization of COMP levels only. Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 44 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…This is Guillaume et al reported that the arthritic group was in remission more often than in other types. Similarly, Aggarwal et al found that 45% of patients in the nonlinear group and 20% of patients in the polyarticular group were in remission [18][19] . In our study the majority of the population had late illnesses and this may be a reason for the presentation of all subtypes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This is Guillaume et al reported that the arthritic group was in remission more often than in other types. Similarly, Aggarwal et al found that 45% of patients in the nonlinear group and 20% of patients in the polyarticular group were in remission [18][19] . In our study the majority of the population had late illnesses and this may be a reason for the presentation of all subtypes.…”
Section: Discussionmentioning
confidence: 83%
“…This is different from the West, where polyarthritis and systemic onset disease are more common than polyarthritis. Moreover, while all the studies in Pakistan, India and Sri Lanka were hospitalized, the studies in Western countries were population-based studies, so comparisons are difficult 18 . Comparing the different subtypes of the active disease group and the remission group, it was found in our study that only one type of disease was not negative.…”
Section: Discussionmentioning
confidence: 99%
“…The ECM components metabolism are related both to the change in the rate of the matrix components degradation processes, which takes place in the presence of excess of ROS (assessed by spectrophotometric method) and proteolytic enzymes-especially MMPs and ADAMTS proteins (assessed by ELISA), as well as to the biosynthesis of matrix compounds [31,32,111]. Treatment that results in clinical stabilization did not contribute to the normalization of markers of cartilage turnover such as chondroitin sulphate [127], keratan sulphate [81], YKL-40 [126] as well as of MMP-3 [43,54], TIMP-1 [60] and TAS concentrations in patients' blood [54]. JIA therapy with the use of methotrexate, glucocorticoids and the non-steroidal anti-inflammatory drugs, may alleviate symptoms by reducing pain and inflammation, but destruction of connective tissues often continues unabated [43,73].…”
Section: Discussionmentioning
confidence: 98%
“…In the course of JIA, there occurred a dysregulation of cartilaginous ECM remodeling, especially aggrecan, manifested by significant changes of the circulating markers of cartilage turnover, including total glycosaminoglycans (assessed by spectrophotometry method) and their particular types such as keratan sulphate (assessed by enzyme-linked immunosorbent assay, ELISA), chondroitin sulphate (assessed by electrophoretic method), hyaluronic acid (assessed by ELISA) as well as chondroitin sulphate 846 epitope (assessed by ELISA) [54,73,81]. Among ECM components, there are also molecules synthesized by chondrocytes, i.e., cartilage oligomeric matrix protein (COMP) and human cartilage glycoprotein 39 (YKL-40) (assessed by ELISA) that can be useful biomarkers of cartilage turnover [126]. These markers can be a useful diagnostic tool to evaluate cartilage condition in JIA patients and could be used to assess treatment towards remission.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were approved by the Local Ethics Committee of the Medical University of Silesia in Katowice (KNW/0022/KB/81/15). Informed consent was obtained from the participants or their legal guardians, according to the ethical guidelines of the Declaration of Helsinki, as part of the continuation of our earlier research [ 16 ].…”
Section: Methodsmentioning
confidence: 99%